Adsorção de pb2+ por nanopartículas de hematita e goetita recuperadas da drenagem ácida de minas - Staub, Chayanne Paula Pavan (2019)
The heavy metals contamination comes mainly from the discharge of industrial effluents in water sources, harming the fauna, flora and human health. The adsorption is a process that presents efficient results in the contaminants removal, and in addition, adsorbents can be obtained at nanometer scales from industrial waste. In this sense, the current work aimed to use nanomaterials, such as hematite and goethite, from acid mine drainage, in the removal of lead metal ions present in a synthetic solution. Hematite and goethite nanomaterials were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and surface area, volume and pore size distribution (BET). The point of zero charge and the pH effect determination were also established for both. In addition, adjustments were performed to the pseudo-first and pseudo-second order kinetic model and of isotherm, the adjustments to the Langmuir and Freundlich models were tested. The results showed that the nanoparticles equilibrium time, for both hematite and goethite, was 500 minutes of adsorption with high removal rates in the initial time, with pH 3 for hematite and pH 4 for goethite. The point of zero charge was below the established pH values, favoring the adsorption of Pb (II) ions, with goethite having the highest removal, reaching 94% and hematite, 92%. The best kinetic setting was the pseudo-second order for both nanoparticles, presenting an R² of 0.92 for hematite nanoparticles and R² of 0.83 for goethite. Experimental data did not fit the Langmuir and Freundlich isotherm models.